Al-Muhassinat al-Lafdziyah fi Maulid al-Dhiya’ al-Lami’ li al-Habib Umar ibn Hafidz Dirasah Badi’iyah - Fathoni Arifandi; Faris Maturedy (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This research focuses on aspects of the beauty of pronunciation contained in the book Mawlid Adh Dhiya'ul Lami' by al Habib Umar bin Hafidz Bin Syekh Abu Bakar bin Salim. Therefore, the researcher aims to describe the beauty of the language in the Mawlid Book. The researcher took the data in the form of the manuscript of the maulid book and then analyzed it using the al muhassinat al lafdziyyah approach in badi' science. The research method used is a qualitative method with a type of literature study. After the analysis process is complete, the researcher draws the conclusion that there are 5 forms of beautiful lafadz, namely saja', murassa', mutawazi, iqtibas and jinas. The form alone 'murassa' is located in 132 places. The mutawazi form lies in 2 places. The iqtibas form is located in 6 places. The forms of both Jinas Naqish and Tam are in one place respectively